Modulation of metabolic communication through gap junction channels by transjunctional voltage; synergistic and antagonistic effects of gating and ionophoresis - Palacios-Prado, Nicolás (2011)
Gap junction (GJ) channels assembled from connexin (Cx) proteins provide a structural basis for direct electrical and metabolic cell-cell communication. Here, we focus on gating and permeability properties of Cx43/Cx45 heterotypic GJs exhibiting asymmetries of both voltage-gating and transjunctional flux (J(j)) of fluorescent dyes depending on transjunctional voltage (V(j)). Relatively small differences in the resting potential of communicating cells can substantially reduce or enhance this flux at relative negativity or positivity on Cx45 side, respectively. Similarly, series of V(j) pulses resembling bursts of action potentials (APs) reduce J(j) when APs initiate in the cell expressing Cx43 and increase J(j) when APs initiate in the cell expressing Cx45. J(j) of charged fluorescent dyes is affected by ionophoresis and V(j)-gating and the asymmetry of J(j)-V(j) dependence in heterotypic GJs is enhanced or reduced when ionophoresis and V(j)-gating work in a synergistic or antagonistic manner, respectively. Modulation of cell-to-cell transfer of metabolites and signaling molecules by V(j) may occur in excitable as well as non-excitable tissues and may be more expressed in the border between normal and pathological regions where intercellular gradients of membrane potential and concentration of ions are substantially altered.